Use of Online Social Media and eHealth Literacy of Urban Youth in Phuket Province, Thailand - Boonwattanopas, Nattawadee (วารสารวิชาการมหาวิทยาลัยอีสเทิร์นเอเชีย ฉบับวิทยาศาสตร์และเทคโนโลยี (online), 2016)
This study investigated online social media use behaviors of youth in urban area of Phuket Province. Participants consist of elementary and high school students, the 4th to 12th graders. Questionnaire was used to collect data from 465 elementary and high school students, the 4th to 12th graders in September 2015. Results showed frequently channels of media exposure through Facebook and Line. Students reported of having Internet connection through Smartphone, at dormitory and home. The most reason of online media use was for entertainment and Internet surf. The majority of students spent time for each activity including 3 - 4 hours for online communication and less than 1 hour for online entertainment and online study/homework assignment. Students’ eHealth literacy was at high level.